Acetophenone benzoylhydrazones as antioxidant agents: Synthesis, in vitro evaluation and structure-activity relationship studies. (1st December 2018) - Emami, Saeed; Esmaili, Zahra; Dehghan, Gholamreza; Bahmani, Maryam; Hashemi, Seyedeh Mahdieh; Mirzaei, Hassan; Shokrzadeh, Mohammad; Moradi, Seyed Ershad
Graphical abstract: Highlights: Some acetophenone benzoylhydrazones 5a-o were synthesized as antioxidant agents. The antioxidant potential of compounds 5a-o was assessed by FRAP and DPPH methods. The unsubstituted compound 5a had the superior capacity in the FRAP assay. The 2, 4-dihydroxyacetophenone analogue 5g was the most potent radical scavenger. 5a and 5g can potently protect HepG2 cells against H2 O2 -induced oxidative damage. Abstract: Acetophenone and its analogues are naturally-occurring compounds found in many foods and plants. In this study, a series of acetophenone benzoylhydrazones 5a-o were designed and synthesized as new potential antioxidant agents. Designed molecules contain hydrazone and phenolic hydroxyl moieties which possibly contribute to antioxidant activity. The antioxidant properties of compounds 5a-o in terms of reducing ability and radical-scavenging activity were assessed by using FRAP and DPPH tests, respectively. While the unsubstituted compound 5a had the superior capacity in the FRAP assay, the 2, 4-dihydroxyacetophenone analogue 5g was the most potent radical scavenger in the DPPH method. The antioxidant potential of representative compounds 5a and 5g was further confirmed by TEAC and ORAC assays. Cell viability assays revealed that while the promising compounds 5a and 5g had no significant toxicity against HepG2 and NIH3T3 cells, they potently protected HepG2 cells against H2 O2 -induced oxidative damage at low concentrations. Furthermore, spectroscopic studies with different biometals demonstrated that 5g was able to interact with Cu 2+ to form a 1:1 complex.